MicroRNA-200a-3p Mediates Neuroprotection in Alzheimer-Related Deficits and Attenuates Amyloid-Beta Overproduction and Tau Hyperphosphorylation via Coregulating BACE1 and PRKACB - Wang, Linlin; Liu, Jianghong; Wang, Qian; Jiang, Hailun; Zeng, Li; Li, Zhuorong; Liu, Rui (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is characterized by two landmark pathologies, the overproduction of amyloid-beta peptides (Aβ), predominated by the β-amyloid protein precursor cleaving enzyme 1 (BACE1), and hyperphosphorylation of the microtubule protein, tau, due to an imbalance in a kinase / phosphatase system that involves the activation of the protein kinase A (PKA). Current evidence indicates that brain microRNAs participate in multiple aspects of AD pathology. Here, the role and underlying molecular mechanisms of microRNA-200a-3p (miR-200a-3p) in mediating neuroprotection against AD-related deficits were investigated. The expression of miR-200a-3p was measured in the hippocampus of APP / PS1 and SAMP8 mice and in an AD cell model in vitro, as well as in blood plasma extracted from AD patients. The targets of miR-200a-3p were determined using bioinformatics and dual-luciferase assay analyses. In addition, cell apoptosis was detected using flow cytometry and related protein levels were measured using Western blot and ELISA techniques. miR-200a-3p was confirmed to be depressed in microarray miRNA profile analysis in vitro and in vivo, suggesting that miR-200a-3p is a potential biomarker of AD. Subsequently, miR-200a-3p was demonstrated to inhibit cell apoptosis accompanied by the inactivation of the Bax / caspase-3 axis and downregulation of Aβ1-42 and tau phosphorylation levels in vitro. Further mechanistic studies revealed that miR-200a-3p reduced the production of Aβ1-42 and decreased hyperphosphorylation of tau by regulating the protein translocation of BACE1 and the protein kinase cAMP-activated catalytic subunit beta (PRKACB) associated with the three prime untranslated regions (3’-UTRs), respectively. Importantly, the function of miR-200a-3p was reversed by overexpression of BACE1 or PRKACB in cultured cells. This resulted in an elevation in cell apoptosis, and an increase in Aβ1-42, and tau hyperphosphorylation levels, involving the epitopes, threonine 205, serine 202, 214, 396, and 356, the favorable phosphorylated sites of PKA. In conclusion, our study suggests that miR-200a-3p is implicated in the pathology of AD, exerting neuroprotective effects against Aβ-induced toxicity by two possible mechanisms: one involving the inhibition of Aβ overproduction via suppressing the expression of BACE1 and; two, synergistically, decreasing the hyperphosphorylation of tau via attenuating the expression of PKA.